2009
DOI: 10.1063/1.3211970
|View full text |Cite
|
Sign up to set email alerts
|

Study on the formation of dodecagonal pyramid on nitrogen polar GaN surface etched by hot H3PO4

Abstract: Hot phosphor acid (H3PO4) etching is presented to form a roughened surface with dodecagonal pyramids on laser lift-off N face GaN grown by metalorganic chemical vapor deposition. A detailed analysis of time evolution of surface morphology is described as a function of etching temperature. The activation energy of the H3PO4 etching process is 1.25 eV, indicating the process is reaction-limited scheme. And it is found that the oblique angle between the facets and the base plane increases as the temperature incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…This observation confirms qualitatively the Gaface character of the GaN surface, as no prominent pyramidal structures can be seen. 14,15,25,26,32 The RMS surface roughness for the free-standing bulk GaN surface was found to be 3.4 6 1.2 nm, which increased to 3.9 6 1.1 nm and 9.1 6 6.5 nm, respectively, after etching with phosphoric acid with and without cysteamine at 40 C. Increasing the temperature treatment to 100 C resulted in decreased roughness to 2.7 6 0.9 nm after treatment with cysteamine, but increased roughness to 13.3 6 6.9 nm after 100 C treatment without cysteamine. Comparing only the effect of treatment in solutions without cysteamine, the surface roughness increases with higher temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation confirms qualitatively the Gaface character of the GaN surface, as no prominent pyramidal structures can be seen. 14,15,25,26,32 The RMS surface roughness for the free-standing bulk GaN surface was found to be 3.4 6 1.2 nm, which increased to 3.9 6 1.1 nm and 9.1 6 6.5 nm, respectively, after etching with phosphoric acid with and without cysteamine at 40 C. Increasing the temperature treatment to 100 C resulted in decreased roughness to 2.7 6 0.9 nm after treatment with cysteamine, but increased roughness to 13.3 6 6.9 nm after 100 C treatment without cysteamine. Comparing only the effect of treatment in solutions without cysteamine, the surface roughness increases with higher temperature.…”
Section: Resultsmentioning
confidence: 99%
“…25 Etched polar GaN has shown increased luminescence over pristine GaN, which produces more efficient optoelectronic devices. 15 Etching processes are sensitive not only to the etchant being used, 12 but also to the temperature, 26 time, 26 and pressure, 27 hence pairing additives with etchants may result in unique properties not seen before. Phosphoric acid acts as the catalyst as well as solvent for dissolved gallium oxide during the etching process.…”
mentioning
confidence: 98%
“…6,7 It is attributed to the facet-selective etching due to the competition between facets that have different surface energy and etching rates. However, we found that it was the dislocation serving as the preferential spatial site for pyramids evolvement initiated the etching process and accelerated the dissociation.…”
Section: D-ds Selective Etchingmentioning
confidence: 99%
“…By comparing the different etching characteristics of Ga-polar and N-polar GaN, Li et al 4,5 has concluded that it was only due to the different states of surface bonding. Zhang 6,7 has found that the N-polar GaN exhibits dodecagonal pyramid feature after etching in H 3 PO 4 instead of conventional hexagonal pyramid feature after etching in KOH. However, there are few researches that deep into the specific etching process of N-polar GaN, for example, the pyramid's shape taking, evolved process and distribution rules, role of dislocation in etching.…”
Section: Introductionmentioning
confidence: 98%
“…7 T. Fujii et al and S. L Qi et al groups have report on texture formation and density in the vertical-type LED (V-LED) to improve the LEE as a function of PEC etching time. 6,8 Although the LEE is associated with the surface status such as size, shape and density in texture, thickness of GaN also can significantly affect the performance of LED. Especially, controlling the texture formation in LED is important because thickness of GaN decreases with increasing an etching time.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%